2022
DOI: 10.3389/fpls.2022.811884
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Physiology and Transcriptome Analysis of Young Spikes in Response to Late Spring Coldness in Wheat (Triticum aestivum L.)

Abstract: Late spring coldness (LSC) is critical for wheat growth and development in the Huang-Huai valleys of China. However, little is known about the molecular mechanisms for young spikes responding to low temperature (LT) stress during anther connective tissue formation phase (ACFP). To elucidate the molecular mechanisms associated with low temperature, we performed a comparative transcriptome analysis of wheat cultivars Xinmai26 (XM26: cold-sensitive) and Yannong19 (YN19: cold-tolerant) using RNA-seq data. Over 400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 116 publications
1
12
0
Order By: Relevance
“…The accumulation of sucrose and soluble sugar in plants under cold stress plays an important role in osmoprotection, maintenance of membrane stability, protein stability, carbohydrate homeostasis and intracellular expansion [ 68 70 ]. Jiang et al [ 71 ] found that the expression of eight genes encoding sucrose synthase and two genes encoding beta-amylases was significantly upregulated in the transcriptome of cold-tolerant wheat, the sucrose content and soluble sugar content were also upregulated in cold-tolerant wheat under cold stress. Wang et al [ 72 ] also found that the expression of SUS6 , SPS1 , AMY3 and BAM2 was significantly upregulated in the transcriptome of cold-tolerant Brassica campestris L. and the soluble sugar content was also upregulated under cold stress, meanwhile starch synthesis was not inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of sucrose and soluble sugar in plants under cold stress plays an important role in osmoprotection, maintenance of membrane stability, protein stability, carbohydrate homeostasis and intracellular expansion [ 68 70 ]. Jiang et al [ 71 ] found that the expression of eight genes encoding sucrose synthase and two genes encoding beta-amylases was significantly upregulated in the transcriptome of cold-tolerant wheat, the sucrose content and soluble sugar content were also upregulated in cold-tolerant wheat under cold stress. Wang et al [ 72 ] also found that the expression of SUS6 , SPS1 , AMY3 and BAM2 was significantly upregulated in the transcriptome of cold-tolerant Brassica campestris L. and the soluble sugar content was also upregulated under cold stress, meanwhile starch synthesis was not inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Here, low-temperature stress causes flower abortion, pollen and ovule sterility, disrupts fertilization and affects seed filling, resulting in poor seed setting and consequently lowered grain yield [56]. Our study showed that the chilling stress (T1) at the anther differentiation period did not significantly reduce SNPP in the two cultivars but could substantially reduce the GNPP in the sensitive cultivar XM26.…”
Section: Discussionmentioning
confidence: 65%
“…The yield reduction rate of the cold-sensitive cultivar was more than 90% at −2 • C for 24 h [5]. This was due to the late development of upper spikelets, less accumulation of nutrients and osmotic adjustment substances [10,56]. Low-temperature stress had different effects on yield and its components in different growth stages of wheat.…”
Section: Discussionmentioning
confidence: 99%
“…ROS is an important product of oxidative stress in plant cells and a key element of programmed cell death. Under normal circumstances, the ROS system is in a state of dynamic equilibrium [ 28 ]. ROS-related indicators in anthers were analyzed to evaluate whether YS3038-A infertility is mediated by the ROS system.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the accumulation rate of ROS in YS3038-A was higher than the scavenging rate, and the dynamic balance between the accumulation and scavenging of ROS was abnormal. Studies have shown that excessive ROS accumulation can lead to abnormal development of anther apoptosis and ultimately lead to male sterility [ 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%